Comprehensive study on the through-process Goss texture evolution in Fe-3.78 wt.%Si grain oriented electrical steel - Jain V.; Kumar P.; Bagui S.; Halder C.; Patra S.; Ghosh A. (My University, 2025)
Cold rolled grain oriented steel is used in transformer cores due to its superior magnetic properties. Large Goss oriented grains develop after the final secondary recrystallization provide low hysteresis loss. The present study represents the development of Goss orientation after each processing stage of Fe-3.78 wt% Si steel with the help of electron backscatter diffraction and x-ray diffraction techniques. The Goss oriented grains developed during hot rolling and hot band annealing did not remain stable in cold rolling. On the other hand, shear bands developed inside {111}<112> component of γ-fiber texture during cold rolling. Partial recrystallization of the cold rolled sheet revealed that Goss oriented grains started evolving inside the shear bands of {111}<112> oriented grains. Intermediate annealing between cold rolling passes was found to be not essential to achieve Goss orientation in primary recrystallization. The optimum primary recrystallization temperature was in between 923 and 948 K where a significant amount of Goss oriented grains were present. Further, secondary recrystallization was attempted at different temperatures between 1173 and 1473 K. Grain boundary curvature of Goss oriented grains and all other grains after both primary and secondary recrystallization was studied. Despite the percentage of convex boundaries surrounding Goss oriented grains was found slightly higher than that around other grains, it was insufficient to cause abnormal grain growth. © 2023 Elsevier B.V.